Feasibility of Microwave-Based Scissors and Tweezers in Partial Hepatectomy: An Initial Assessment on Canine Model - Dang, Khiem Tran; Naka, Shigeyuki; Yamada, Atsushi; Tani, Tohru (Frontiers in Surgery, 2021)
Purpose: This study aimed to assess the feasibility of partial hepatectomy (PH) simplified by using microwave-based devices in animal experiments. Methods: PH was performed on 16 beagles using either Acrosurg Scissors (AS) or Acrosurg Tweezers (AT) without hepatic pedicle (HP) control. Parenchymal transection time, Glissonean pedicle (GP) seal time, bleeding volume, bile leak, and burst pressure were recorded. Probable complications were investigated after four weeks. Results: Transection time (6.5 [6.0 – 7.6] vs. 11.8 [10.5 – 20.2] min, p < 0.001) with AT were significantly shorter than with AS. GP sealing times (60 [55 – 60] vs. 57 [46 – 91] s, p = 0.859) by both devices were nearly similar. Bleeding volume in the AT group was approximately one-fourth of that in the AS group (6.7 [1.4 – 22] vs. 28.8 [5.8 – 48] mL, p = 0.247). AT created higher burst pressure on the bile duct stumps (p = 0.0161). The two devices did not differ significantly in morbidity and mortality after four-week follow-up. Conclusion: Acrosurg devices achieved a safe PH without HP control owing to microwave-based sealing. AS could be used alone in PH, whereas the clamp-crushing function of AT seemed more advantageous in reducing the transection time and blood loss.